2020
DOI: 10.4103/ijo.ijo_1840_19
|View full text |Cite
|
Sign up to set email alerts
|

Endophthalmitis with opaque cornea managed with primary endoscopic vitrectomy and secondary keratoplasty: Presentations and outcomes

Abstract: Purpose: To describe the outcomes of endophthalmitis with opaque cornea managed with primary endoscopic vitrectomy and secondary keratoplasty. Methods: Retrospective consecutive interventional case series. All cases of endophthalmitis with opaque cornea which underwent endoscopic vitrectomy followed by secondary keratoplasty were analyzed. The study period was from Jan 2015 to March 2019. The outcome measures were resolution of infection, the magnitude of unnecessary ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…2 In endoph thalmitis, endoscopicassisted vitrectomy can be critical to clear vitreous pathogens, take cultures, reduce inflammation, and repair retinal detachments (RDs). 17,[20][21][22][23] A recent retro spective study of 33 eyes with endophthalmitis managed with endoscopicassisted vitrectomy suggested that the use of the modality allowed for earlier intervention in cases with poor visualization, which likely reduces the organism load and helps contain the infection. 24 In RD repair, endoscopy is useful, 25 with some studies suggesting improvement in outcomes 26,27 and visualization of retinal breaks.…”
Section: Discussionmentioning
confidence: 99%
“…2 In endoph thalmitis, endoscopicassisted vitrectomy can be critical to clear vitreous pathogens, take cultures, reduce inflammation, and repair retinal detachments (RDs). 17,[20][21][22][23] A recent retro spective study of 33 eyes with endophthalmitis managed with endoscopicassisted vitrectomy suggested that the use of the modality allowed for earlier intervention in cases with poor visualization, which likely reduces the organism load and helps contain the infection. 24 In RD repair, endoscopy is useful, 25 with some studies suggesting improvement in outcomes 26,27 and visualization of retinal breaks.…”
Section: Discussionmentioning
confidence: 99%